EUCLIDEAN SPACE: SEQUENCES IN R^m SPACE AND IMPORTANT SETS IN R^m SPACE - Abdullayeva Madinaxon Mamirjon Qizi (Antis Publisher, 2025)
Objective: This article aims to provide comprehensive insights into the Euclidean space Rm, serving as a resource for students, educators, and researchers in mathematical analysis and linear algebra. Method: Fundamental concepts and properties of Rm are elaborated, including sequences, distance properties, and the characteristics of open and closed sets. The analysis incorporates mathematical frameworks to examine bounded and unbounded sets alongside hyperplanes within Rm. Results: The study elucidates the key mathematical constructs and properties that define R^m, offering a structured understanding of its theoretical and practical applications in mathematics. Novelty: This work stands out by consolidating essential definitions and properties of Rm in a single resource, bridging gaps between foundational and advanced topics in mathematical analysis.